Cityscapes and Monuments of Western Asia Minor : Memories and Identities - Mortensen, Eva (Oxbow Books, Limited, 2017)
Front cover -- Title -- Copyright -- Contents -- List of Abbreviations -- List of Contributors -- Preface -- Part I Introduction -- 1 Constructing Memories: Gateways between Identity and Socio-Political Pluralism in Ancient Western Asia Minor Martina Seifert -- Part II Cityscapes of Remembrance -- 2 Cityscape and Places of Memory in Assos Eva-Maria Mohr, Klaus Rheidt and Nurettin Arslan -- 3 Nothing to Remember? Redesigning the Ancient City of Assos in the Byzantine Era* Beate Böhlendorf-Arslan -- 4 Glory be to (Insert Name Here): Civic Memory, Political Discourse and Municipal Ruler Cult in Hellenistic Teos* Anthony Shannon -- 5 Das Stadtbild von Magnesia am Mäander nach den 30-jährigen Ausgrabungen (Kurzfassung)Orhan Bingöl -- 6 Narratives and Shared Memories of Heroesin the Aphrodisian Cityscape Eva Mortensen -- 7 The City of Xanthus: "Lieu de mémoire" of the Lycians Jacques des Courtils -- 8 Expressing Civic Self-Perception and ConstructingIdentity - Public Imagery in Roman Asia Minor Kai M. Töpfer -- Part III Recollections of the Past in Public Civic Monuments -- 9 Gymnasia: From a Space to an Institution of Remembrance* Ulrich Mania -- 10 Representing and Remembering Rituals in Public Space: Depictions of Sacrifice in Roman Asia Minor* Günther Schörner -- 11 Aspects of Public Memory at the East Gate of Side Ute Lohner-Urban -- Part IV Representations of Memories and Identities in the Private Sphere -- 12 Identity in the Private Sphere: Interpreting Houses as Loci Reflecting the Identity of Their Inhabitants Elisabeth Rathmayr -- 13 A P(a)lace of Remembrance? Reflections on the Historical Depth of a Monumental Domus in Ephesos* Christoph Baier -- Part V Narratives of Remembrance in a Religious Context -- 14 Die Sitzstatue eines Dichters aus Klaros* Ergün Laflı.